2017
DOI: 10.1038/mp.2017.111
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic evidence for the involvement of schizophrenia risk genes in antipsychotic effects

Abstract: Genome-wide association studies (GWAS) for schizophrenia have identified over 100 loci encoding >500 genes. It is unclear whether any of these genes, other than dopamine receptor D2, are immediately relevant to antipsychotic effects or represent novel antipsychotic targets. We applied an in vivo molecular approach to this question by performing RNA sequencing of brain tissue from mice chronically treated with the antipsychotic haloperidol or vehicle. We observed significant enrichments of haloperidol-regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…A popular bioinformatics tool for constructing and studying gene coexpression networks is Weighted Gene Co-Expression Analysis (WGCNA) [6]. This approach has been used to characterize patterns of co-expression in the normal brain [7], in autism spectrum disorders [8], in schizophrenia (human and animal modeling studies) [9][10][11][12] and across mental disorders [13]. Importantly, co-expression network analysis has also been used to understand the partitioning of polygenic SCZ risk in the brain transcriptome.…”
Section: Introductionmentioning
confidence: 99%
“…A popular bioinformatics tool for constructing and studying gene coexpression networks is Weighted Gene Co-Expression Analysis (WGCNA) [6]. This approach has been used to characterize patterns of co-expression in the normal brain [7], in autism spectrum disorders [8], in schizophrenia (human and animal modeling studies) [9][10][11][12] and across mental disorders [13]. Importantly, co-expression network analysis has also been used to understand the partitioning of polygenic SCZ risk in the brain transcriptome.…”
Section: Introductionmentioning
confidence: 99%
“…Since SCZ patients are usually treated with antipsychotics, it can be hypothesized that drugs contributed to the aggregation of genes into modules. In a recent study, Kim and coworkers ( 30 ) identified genes differentially expressed in the striatum and in the whole brain of mice exposed to haloperidol vs. not exposed mice. We computed for all modules the enrichment for the differentially expressed genes and found a single module ( Brown ) enriched (11 genes, 16% of total differentially expressed genes, Bonferroni-corrected p-value = .00447, Data file S4).…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, both findings highlight the potential importance of the genes co-expressed in Darkgreen for the physiology of olanzapine and clozapine, two atypical antipsychotics. Darkgreen included also genes coding for proteins involved in synaptic transmission mediated by serotonin, glutamate and GABA ( HTR1F , GRM5 , GABRB1 , GABRG3 ), or involved in neural excitability ( KCNH1 , KCNA3 , KCNH7 , KCNH5 ), along with CACNA1C , a risk gene for SCZ and bipolar disorder supported by multiple lines of evidence ( 4044 ). The functions of the genes in Darkgreen are consistent with previous pathway analyses of SCZ risk ( 45 ) and enhance the biological plausibility that the coregulation of this module has functional relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies performed using the region of interest method showed that common variants in the MHC gene family had a significant relationship with decreased thalamus and hippocampal volumes in schizophrenia patients (Brucato, Guadalupe, Franke, Fisher, & Francks, 2015;Walters et al, 2013). In addition, the schizophrenia patients in these studies mostly received antipsychotic treatment, and this might have had an impact on illness-related gene expression, protein phosphorylation, and new protein synthesis in addition to further effects on the mediation cerebral development and functional maturation (Kari, Silje, Christine, & Vidar, 2017;Kim, Giusti-Rodriguez, & Crowley, 2018).…”
Section: Introductionmentioning
confidence: 99%